Insights into the UO2+x/U4O9 phase characterization in oxidized UO2 pellets as a function of hyper-stoichiometry - Gaillard, C.; Lotz, H.; Sarrasin, L.; Pipon, Y.; Ducher, R.; Moncoffre, N. (Frontiers in Nuclear Engineering, 2024)
We present new insights on the study of the UO2+x/U4O9 equilibrium in UO2 as a function of the hyperstoichiometry x, by coupling HERFD-XANES at the uranium M4-edge and micro-Raman spectroscopy mapping. XANES allowed to measure the uranium speciation in the samples while Raman spectroscopy was used to characterize individually the composition and localization of the different oxide phases. UO2 pellets were oxidized under dry conditions at temperatures above the UO2+x/U4O9 phase transition to reach hyper-stoichiometries in the range 0.01  x  0.1. Combining both technics, we could determine the proportion between U4O9 and UO2+x. We show that at low O/U ratio, U4O9 is present as small clusters inside UO2 grains. As the O/U increases, we evidence the formation of a network of U4O9 crystallized inside UO2+x grains. The variation of the UO2+x phase hyperstoichiometry (x) was evaluated as a function of the sample oxidation.